2009
DOI: 10.1016/j.exer.2008.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The α1 isoform of the Na+/K+ ATPase is up-regulated in dedifferentiated progenitor cells that mediate lens and retina regeneration in adult newts

Abstract: Adult newts are able to regenerate their retina and lens after injury or complete removal through transdifferentiation of the pigmented epithelial tissues of the eye. This process needs to be tightly controlled, and several different mechanisms are likely to be recruited for this function. The Na + / K + ATPase is a transmembrane protein that establishes electrochemical gradients through the transport of Na + and K + and has been implicated in the modulation of key cellular processes such as cell division, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…FGF‐dependent neural regeneration activated the MAPK pathway. Furthermore, inhibition of a downstream transducer, MEK, blocks FGF‐dependent retinal regeneration (Vergara & Del Rio‐Tsonis, ). As the CMZ was ablated in this model, the likely source of progenitor cell population is the RPE.…”
Section: Retinal Regenerationsupporting
confidence: 93%
See 2 more Smart Citations
“…FGF‐dependent neural regeneration activated the MAPK pathway. Furthermore, inhibition of a downstream transducer, MEK, blocks FGF‐dependent retinal regeneration (Vergara & Del Rio‐Tsonis, ). As the CMZ was ablated in this model, the likely source of progenitor cell population is the RPE.…”
Section: Retinal Regenerationsupporting
confidence: 93%
“…Another model of retinal regeneration was developed by Vergara and Del‐Rio Tsonis, which used a new surgical approach where retinectomy also removed the CMZ. In this case, retinal regeneration only occurred in the presence of FGF induction using FGF2‐soaked beads as a growth factor source (Vergara & Del Rio‐Tsonis, ). FGF‐dependent neural regeneration activated the MAPK pathway.…”
Section: Retinal Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the a1 isoform of the Naþ/Kþ ATPase is upregulated in dedifferentiated progenitor cells. 27 Further study is necessary to investigate the mechanism of increased Na þ -K þ ATPase and COL8A2 expression. Proliferation rates were different depending on the medium used.…”
Section: Discussionmentioning
confidence: 99%
“…Na + channels have been used to monitor ganglion cell differentiation during RPE transdifferentiation [129,130,139]. In contrast, a study by Vergara et al [140] reported that the α subunit of the Na + /K + -ATPase is up-regulated transiently in the RPE during early transdifferentiation when retinal progenitors form, but is not present in the intact RPE or neural retina. It must be noted that more research is required to elucidate further the role of these channels/transporters during retina regeneration.…”
Section: Amphibiansmentioning
confidence: 99%